Discovery of pyrazines as pollinator sex pheromones and orchid semiochemicals: Implications for the evolution of sexual deception - Bohman, B.; Philips, R.; Menz, M.; Flematti, G.; Barrow, R.; Dixon, Kingsley; Peakall, R. (Wiley-Blackwell Publishing Ltd., 2014)
Sexually deceptive orchids employ floral volatiles to sexually lure their specific pollinators. How and why this pollination system has evolved independently on multiple continents remains unknown, although preadaptation is considered to have been important. Understanding the chemistry of sexual deception is a crucial first step towards solving this mystery. The combination of gas chromatography-electroantennographic detection (GC-EAD), GC-MS, synthesis and field bioassays allowed us to identify the volatiles involved in the interaction between the orchid Drakaea glyptodon and its sexually attracted male thynnine wasp pollinator, Zaspilothynnus trilobatus. Three alkylpyrazines and one novel hydroxymethyl pyrazine were identified as the sex pheromone of Z. trilobatus and are also used by D. glyptodon for pollinator attraction. Given that our findings revealed a new chemical system for plants, we surveyed widely across representative orchid taxa for the presence of these compounds. With one exception, our chemical survey failed to detect pyrazines in related genera. Collectively, no evidence for preadaptation was found. The chemistry of sexual deception is more diverse than previously known. Our results suggest that evolutionary novelty may have played a key role in the evolution of sexual deception and highlight the value of investigating unusual pollination systems for advancing our understanding of the role of chemistry in evolution.